The Influence of Transformational Leadership and Perceived Organizational Support (POS), Mediated by Trust on Employee Engagement at PT Hutama Karya (Persero) - Khoerunnisa, Sarah; Yusnita, Nancy; Hadiyat, Yayan (International Journal Administration, Business & Organization, 2025)
This study aims to analyze the influence of transformational leadership and Perceived Organizational Support (POS) on employee engagement, with trust as a mediating variable. A quantitative research approach was employed using a survey technique. Data were collected through questionnaires distributed to employees of PT Hutama Karya (Persero) and analyzed using Structural Equation Modeling (SEM). The findings indicate that transformational leadership and POS have a positive and significant impact on trust, which in turn enhances employee engagement. Trust is proven to be a mediator that strengthens the relationship between transformational leadership, POS, and employee engagement. The study concludes that organizations need to reinforce transformational leadership and provide better organizational support to foster employee trust, ultimately leading to higher engagement. These findings offer practical implications for PT Hutama Karya (Persero) management in designing strategies to enhance employee engagement and support the company's business sustainability.